Interferensi pada Multilingualisme Santri Tmi Al-Amien dan Peran KH. Moh. Marzuqi Maâ€™ruf dalam IshlÄh Al-Akhthaâ€™ Bahasa Arab - Abdul Kirom (Maharot : Journal of Islamic Education, 2020)
This article aims to describe the form of oral Arabic interference in the multilingualism of the students of TMI Al-Amien Prenduan and role of KH. Mohammad Marzuqi Ma'ruf in correcting the interference they experienced with the ishalahul akhtha' program. The researcher used a descriptive qualitative field study with data collection techniques in the form of interviews with several TMI Language Markaz ustadz, utilizing important documents related to this research, and the researcher himself became an active participant in field observations as a teacher at TMI. The results of this study indicate that, firstly among TMI students in using Arabic there is morphological, syntactic and cultural interference. Second, the role of KH. Mohammad Marzuqi Ma'ruf in correcting the interference is reflected in the ishalaul akhtha' program which runs throughout the year there. His role is also strongly supported by the existence of strict linguistic regulations which are reflected in the provision of punishment and reward. He is a productive figure in his work, and his works become the main ingredient in the ishalaul akhtha' program.Â Â